Unlocking Excellence: The Impact of Teacher Competence on Learning and Leadership - Marwan Marwan; Deviyantoro Deviyantoro (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study investigates the dual impact of teacher competence on student academic performance and the development of leadership qualities in Senior High Schools and Vocational High Schools in Kabupaten Serang, Banten Province. Using a qualitative research approach, data were collected through interviews, focus groups, and classroom observations involving teachers and students. The findings reveal that teacher competence encompasses not only mastery of subject matter and pedagogical skills but also emotional intelligence and leadership modeling. Competent teachers create supportive and participatory learning environments that enhance both academic achievement and leadership development among students. The research highlights that effective teachers are those who not only deliver content but also engage students in meaningful ways, fostering a sense of belonging and motivation. This engagement is crucial, as it encourages students to take ownership of their learning and develop critical thinking skills. Furthermore, the study identifies that teachers who model leadership behaviors—such as ethical decision-making, effective communication, and collaboration—significantly influence students' perceptions of leadership and their willingness to adopt similar traits. However, challenges such as limited access to professional development and resource constraints affect the full realization of teacher competence. Many teachers express a desire for ongoing training and support to enhance their skills, yet systemic barriers often hinder their professional growth. The study underscores the need for comprehensive teacher development programs and policy support to improve educational outcomes holistically. These insights are valuable for educators, policymakers, and school administrators aiming to foster academic excellence and leadership skills in students. By prioritizing teacher competence and providing the necessary resources, schools can create an environment that not only promotes academic success but also prepares students to become effective leaders in their communities.